Analisis Efisiensi Penggunaan Bucket terhadap Kegiatan Pemuatan Curah Kering Klinker di PT Berlian Manyar Sejahtera - Deva Yuan Mahardika; Elly Kusumawati; Antony Damanik (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Loading and unloading activities are activities carried out on land, sea and air (Permenhub). In the field of loading and unloading, one of the loading and unloading companies will be observed, namely the company PT. Berlian Manyar Sejahtera plays a big role in supporting the needs of loading and unloading activities for handling clinker dry bulk cargo. One of the tools that supports clinker dry bulk loading activities is by using a bucket. A bucket is a tool that can support clinker dry bulk loading activities. where this tool functions to transport dry bulk clinker to the truck properly. The research method used is the Quantitative Method which explains Bucket Efficiency in dry bulk clinker loading activities at PT Berlian Manyar Sejahtera. Data collection techniques through observation, documentation, interviews and questionnaires. The results of this research show that buckets are more efficient than using grabs because in the dry bulk loading process the clinker bucket has a target which can be realized according to the target, whereas for grabs the target and income are bigger but cannot be realized properly according to the target. The advice given is to prepare supporting equipment such as grabs and well-maintained buckets because this can support clinker dry bulk loading activities and additional loading and unloading workers are needed so that the clinker dry bulk loading process will be more efficient and faster.